UTILIZATION OF INFORMATION TECHNOLOGY AS A LEGAL EDUCATION MEDIA CONSUMER PROTECTION - Teddy Prima Anggriawan; Anajeng Esri Edhi Mahanani; Retno Mumpuni; Alvian Dwiangga Wijaya (UNTAG Law Review, 2021)
Globalization is currently running in cyberspace, connecting all digital communities. All aspects of human life are influenced by internet information technology, in this case the economic conditions provide very significant changes. Online stores or what we often call e-commerce is a form of change brought about by the internet in terms of shopping innovation by providing various conveniences in the transaction process. Seeing the phenomenon of the rapid development of electronictransactions in Indonesian society, the problem in this research is how to use information technology as a media for consumer protection law education. The research method applied in this study is a normative legal research method. The research is said to be juridical normative because it intends to study and analyze the substance of the legislation on the subject matter or legal issue in its consistency with existing legal principles. The type of research used in this writing is doctrinal research.Aims to obtain a systematic explanation of the rule of law. Thus, all benefits to the community will depend on the provisions of the law itself. The element of education then becomes the spearhead to instill attitudes and habits of obedience to existing rules. If all human interests can be fulfilled without disputes or conflicts, then everything that happens regularly will not be questioned about the concept of justicewhich focuses on what is entitled or who is at fault if someone is harmed by another person. The first indicator is an understanding of the law, a person knows about certain behaviors that have been regulated by law.